Draft Annual Plan 2005-2006 - Planning Commission (Planning Commission, 2005)
"The state was formed on 1st November 2000 with a geographical area of 137 thousand sq. km. which accounts for 4% of the country's area. A per 2001 Census the state has population of 2.08 crores which accounts for 2.03 per cent population of the country. Density of population is 154 per sq. km. as against national average of 324. Scheduled Tribe population is 31.76% against national average of 8.08% Scheduled Caste population is 11.61% against national average of 16.5% About 38% population is living below poverty line. About 82% people depend for their sustenance on Agriculture and forest.
Government of Chhattisgarh